2009
DOI: 10.1016/j.ydbio.2008.11.013
|View full text |Cite
|
Sign up to set email alerts
|

A conserved nuclear receptor, Tailless, is required for efficient proliferation and prolonged maintenance of mushroom body progenitors in the Drosophila brain

Abstract: The intrinsic neurons of mushroom bodies (MBs), centers of olfactory learning in the Drosophila brain, are generated by a specific set of neuroblasts (Nbs) that are born in the embryonic stage and exhibit uninterrupted proliferation till the end of the pupal stage. Whereas MB provides a unique model to study proliferation of neural progenitors, the underlying mechanism that controls persistent activity of MB-Nbs is poorly understood. Here we show that Tailless (TLL), a conserved orphan nuclear receptor, is req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 75 publications
6
47
1
Order By: Relevance
“…6F). Consistent with the known requirement of Tll for MB neurogenesis (Kurusu et al, 2009), the SoxN-positive MBs showed reduced neuron numbers and aberrant morphologies (data not shown). This exemplifies the importance of lineage-specific expression or repression of various TFs in programming distinct NBs and their production of lineage-characteristic progenies.…”
Section: Tfs Differentially Expressed In Distinct Nbssupporting
confidence: 82%
See 1 more Smart Citation
“…6F). Consistent with the known requirement of Tll for MB neurogenesis (Kurusu et al, 2009), the SoxN-positive MBs showed reduced neuron numbers and aberrant morphologies (data not shown). This exemplifies the importance of lineage-specific expression or repression of various TFs in programming distinct NBs and their production of lineage-characteristic progenies.…”
Section: Tfs Differentially Expressed In Distinct Nbssupporting
confidence: 82%
“…6B′). By contrast, Tll is abundant in the offspring of MB NBs (Kurusu et al, 2009) (Fig. 6C, arrows) and the developing optic lobe (Li et al, 2013), but could not be detected within the AL lineages (Fig.…”
Section: Tfs Differentially Expressed In Distinct Nbsmentioning
confidence: 95%
“…Prospero, which encodes a homeodomain transcription factor associated with the differentiation of ganglion mother cells after asymmetric stem cell division of neuroblasts in the central brain [42,43], is the only target gene that has been found to be directly regulated by Tll in postembryonic stages [44]. In the mouse, multiple genes involved in the development of the CNS and visual system have been identified as Tlx targets, such as Gsh2, Pax2, Pten, p21, p57, S100b, Aqp4, Plce1, Wnt7a, microRNA-9, Bmp4, and GFAP [21,[32][33][34][35][36][37][45][46][47][48][49][50] (Table 1).…”
Section: Tlx Expression Its Targets and Related Signal Pathwaysmentioning
confidence: 99%
“…In contrast, in the ganglion mother cells derived from neuroblasts through asymmetric division, a lack of tll expression and elevated prospero expression promote differentiation [42,43]. It has been reported that ectopic expression of tll in ganglion mother cells inhibits apoptosis, promotes cell-cycle progression, and results in tumor formation in the Drosophila brain [44].…”
Section: Roles Of Tlx Homologues In the Regulation Of Nscs And Brain mentioning
confidence: 99%
“…In the developing brain, at stage 13 CORL first appears in one or two cells within the ventral-most part of the trito-and deutocerebrum, and in small groups of cells in lateral regions of the ocular protocerebrum ( Fig (18) neurons and toy mutants die with visible MB defects (FurukuboTokunaga et al, 2009). The MB is the site of many cognitive functions and receives input from a variety of sources (Truman et al, 1994;Davis, 1996).…”
Section: Corl Embryonic Expression Is Restricted To the Central Nervomentioning
confidence: 99%